2009
DOI: 10.1590/s1980-57642009dn30400002
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging for Alzheimer's disease: A review of concepts and potential clinical applicability

Abstract: In view of the urgent need to identify an early and specific biomarker for Alzheimer’s disease (AD), a PubMed database search was performed using the terms “Alzheimer disease” and “Diffusion Magnetic Resonance Imaging” to enable review of Diffusion tensor imaging (DTI) concepts and its potential clinical role in AD evaluation. Detailed analysis of selected abstracts showed that the main DTI measures, fractional anisotropy and apparent diffusion coefficient, indicators of fiber tract integrity, provide a direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Further, diffusion tensor imaging and magnetic transfer imaging (MTI) studies can quantify white matter microstructural changes which are believed to reflect mostly ischemic demyelination, axonal loss, and gliosis. Investigations using diffusion tensor imaging showed AD-related changes in temporal areas, parietal areas, frontal areas, the corpus callosum, cingulate gyrus/cingulate fiber tracts, uncinate fasciculus, inferior longitudinal fasciculus/superior longitudinal fasciculus fiber pathways, hippocampus, thalamus, basal ganglia, and internal capsule (for a review, see [12]). A study using MTI revealed a decrease in the bilateral magnetization transfer ratio of AD patients in the temporal, cingulate, parietal, and prefrontal white matter regions, and these results indicated a widespread decrease of white matter myelination in AD [13].…”
Section: Introductionmentioning
confidence: 99%
“…Further, diffusion tensor imaging and magnetic transfer imaging (MTI) studies can quantify white matter microstructural changes which are believed to reflect mostly ischemic demyelination, axonal loss, and gliosis. Investigations using diffusion tensor imaging showed AD-related changes in temporal areas, parietal areas, frontal areas, the corpus callosum, cingulate gyrus/cingulate fiber tracts, uncinate fasciculus, inferior longitudinal fasciculus/superior longitudinal fasciculus fiber pathways, hippocampus, thalamus, basal ganglia, and internal capsule (for a review, see [12]). A study using MTI revealed a decrease in the bilateral magnetization transfer ratio of AD patients in the temporal, cingulate, parietal, and prefrontal white matter regions, and these results indicated a widespread decrease of white matter myelination in AD [13].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of diffusion imaging studies in AD (Vasconcelos et al ., 2009), the majority of which have compared AD and similar aged controls or with subjects with mild cognitive impairment. The most consistent findings are that posterior brain regions seem to be more affected than anterior regions during the early stages of AD, then, as the disease progresses, the limbic and frontal structures also become involved followed lastly by the primary sensorimotor regions, which have been shown to correlate with the clinical manifestations of the disease (Medina and Gaviria, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with the findings of previous studies; both found that the FA values of patients with AD are reduced ( Naggara et al, 2006 ; Ukmar et al, 2008 ; Liu et al, 2011 ; Brueggen et al, 2019 ). Past studies have also shown that cognitive function is associated with diffusion indexes ( Vasconcelos et al, 2009 ; Ling et al, 2011 ; Mayo et al, 2019 ), suggesting that white matter damage adversely affects cognitive function. FA reflects the dispersion direction of the white matter, the regular and organized white matter has higher FA values, and if the structure of the white matter becomes disordered, FA values will decrease.…”
Section: Discussionmentioning
confidence: 97%